Andrzej Wajda. Sketcher - Bogna Dziechciaruk-Maj (Przestrzenie Teorii, 2017)
The author discusses a little-known aspect of Andrzej Wajda’s work – his drawings and sketches, which he produced throughout his life. What is striking about these works is the diverse nature of their subject matter (his efforts as a student, drawings related to theatre and film, landscapes, portraits) and techniques (fountain pen, marker pen, chalk, watercolours). These constitute an important element of how he expressed himself, they are a way to record reality, and complement his work as a director superbly. These sketches were presented on many occasions in exhibitions in Poland and abroad. The wealth of creativity in Andrzej Wajda’s drawings was best seen in the exhibition organised in the Manggha Museum on his 90th birthday, entitled “Andrzej Wajda. Sketcher” (March–August 2016).